Клинико-психопатологическая структура и типология исходов манифестных прогредиентных форм шизофрении - А. Г. Мкртчян (Հայաստանի ԳԱԱ)
Կլինիկա-հոգեախտաբանական, կլինիկա-կատամնեստիկ և փսիխոմետրիկ մեթոդներով հետազոտվել են շիզոֆրենիայի մանիֆեստային պրոգրեդիենտ ձևերով տառապող 243 հոսպիտալացված քրոնիկական հիվանդ՝ հիվանդության հեռավոր շրջաններում: The study applied clinical-psychopathological, clinical-cathamnestic and psychometric testing approaches to examine 243 institutionalized chronic patients with manifested progredient forms of schizophrenia in residual phase of the disease.
Keywords: Internal medicine; Medicine; Neuroscience; Biological psychiatry; Neuropsychiatry